Urinary Tract Stone Disease 2010
DOI: 10.1007/978-1-84800-362-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Renal Stones

Abstract: Drug-induced stones represent about 1% of all renal stones. They involve two main mechanisms. The first one includes stones made of the drug and/or its metabolites identified by X-ray diffraction or infrared spectroscopy on the basis of their specific diagrams. Nowadays, the most commonly observed ones are antiproteases (such as indinavir) used in HIV-infected patients, high-dose sulfadiazine used for the treatment of cerebral toxoplasmosis, and abuse of ephedrine/guaifenesin-containing preparations, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 126 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Only 1-2% of all urinary stones have been reported to be induced by medications 31 (Table 1). However, evidence has emerged that a number of drugs seem to have a tendency to cause crystalluria.…”
Section: Types Of Urinary Stonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1-2% of all urinary stones have been reported to be induced by medications 31 (Table 1). However, evidence has emerged that a number of drugs seem to have a tendency to cause crystalluria.…”
Section: Types Of Urinary Stonesmentioning
confidence: 99%
“…However, evidence has emerged that a number of drugs seem to have a tendency to cause crystalluria. Stone formation induced by drugs can occur in two ways: drugs (such as loop diuretics, uricosurics, carbonic anhydrase inhibitors, antiobesity drugs, and laxatives) 31 can induce metabolic abnormalities that can lead to the formation of stones; and supersaturation of urine with the drug (which can be due to drug insolubility) can induce the precipitation of crystals comprised of the drug itself, which can then lead to stone formation (for example, stones made of drugs such as acyclovir, atazanavir, indinavir, methotrexate, triamterene, and ciprofloxacin) 31,32 . Risk factors for drug-induced stone formation include high daily drug doses, low drug solubility, long-term treatment, high levels of drug excretion via the urine, and low urine volume 31 .…”
Section: Types Of Urinary Stonesmentioning
confidence: 99%
“…1) most commonly comprise calcium oxalate (65%) but can also contain calcium phosphate (10%), uric acid (15%), magnesium ammonium phosphate (10%), cystine (1%), 2,8-dihydroxyadenine (<1%), xanthine (<1%), or excreted drugs such as indinavir (<1%) [6][7][8][9][10] . The composition of kidney stones shows worldwide geographical variation and although the proportion of calcium oxalate stones has been reported to be relatively consistent between countries, magnesium ammonium phosphate stones, which are associated with infection, are more frequent in Sub-Saharan Africa than in more developed regions 11 Unsurprisingly, therefore, nephrolithiasis is often associated with metabolic abnormalities of urinary solute concentration or decreased urinary solubility; these abnormalities include hypercalciuria, hyperoxaluria, hypocitraturia, hyperuricosuria, cystinuria, low urinary volume and defects in urinary acidification 8,12 .…”
Section: [H1] Introductionmentioning
confidence: 99%
“…On the other hand, some drugs have compounds that have metabolic effects on urine pH and excretion of calcium, oxalate, phosphate, citrate, uric acid and other purines. The formation of drug‐induced kidney stones is usually caused by the use of high doses of drugs, prolonged treatment, high renal excretion, low solubility of the drug and/or its metabolites, low urine output and inappropriate level of urine pH 56 . In the study by Muhbes, a positive correlation was observed between the use of antacids and aspirin and the formation of renal stones 15…”
Section: Discussionmentioning
confidence: 99%